Atributos químicos do solo e resposta da sucessão milho-cevada-feijão-trigo influenciados por doses e parcelamento de gesso em plantio direto - Michalovicz, Leandro (2012)
The effects of gypsum rates and splitting on chemical attributes of a Brown Latossol under no-till system, along with nutrition and yield of maize, barley, bean and wheat were evaluated between 2009 and 2011 at Guarapuava, Paraná State, Brazil. A randomized complete block design experiment was used, with four replications. The treatments were constituted by four rates of gypsum (3, 6, 9 and 12 Mg ha?¹), applied without and with splitting (50% + 50% - in two years), plus a control treatment without gypsum. Soil sampling was performed in layers between 0,0-0,8 m depth, at six and 18 months after the first gypsum application. Leaf content of nutrients and grain yield of crops were also evaluated. Results were submitted to analysis of variance and regression. Gypsum rates promoted small magnitude increase of soil pH at subsuperficial layers, and also increased levels of Ca²+ and S-SO4 2- in all evaluated soil layers, without effect of splitting only for Ca²+ at layers between 0,4-0,8 m depth. Soil levels of Al³+, Mg²+ and K+ decreased in some layers with gypsum addition, and levels of P in the soil were increased only at 0,0-0,1 m layer at 18 months after application. Splitting gypsum rates decreased movement intensity of Ca²+, Mg²+ and S-SO4 2- towards subsurface layers, mainly between 0,4-0,8 m depth. Gypsum increased N and P concentrations in the leaves of beans, showing positive effect of splitting for N. Leaf levels of Ca, S and the Ca/Mg ratio in leaves were increased in all crops evaluated with gypsum application, with positive effect of splitting for leaf concentration of S. Leaf levels of Mg decreased in maize, bean and wheat, with negative effect of splitting for wheat. There was no effect of treatments on leaf concentration of K, in all crops evaluated. Maize, barley and wheat yields showed quadratic response to gypsum rates, with grain yields 11%, 10% and 10% higher in relation to control treatment, respectively, without effect of splitting the rates of gypsum. There was no effect of treatments on the yield of beans. Cumulative yield showed quadratic response to gypsum rate increase, with maximum yields estimated with 6,5% and 9,6% increase in relation to control treatment for non splitted and splitted rates, respectively.